ANALISIS PENERAPAN METODE COOPERATIVE LEARNING DALAM MENINGKATKAN KEAKTIFAN SISWA PADA PELAJARAN PAI - Visca Anisa Mareta; Abdul Kodir Nurhasan; Yal Robiansyah; Andriani, Luh Ade Yuanita (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
This study discusses the application of the Cooperative Learning method in increasing student activity in PAI learning for grade 3 and 4 students at MI Fathan Mubina Ciawi Bogor for the 2022/2023 academic year. The background is the low level of student enthusiasm for PAI subjects, which is caused by a lack of student interest in learning. This is because the teacher's implementation of the learning methods is less precise, causing students to feel bored and bored. Student boredom and boredom are one of the obstacles to the learning process. Novelty in this research focuses on seeing student activeness influenced in the long term by applying cooperative learning consistently. This research is a type of qualitative research using observation, interview and document data collection techniques.The data collection technique is aimed at the teachers and students concerned to obtain data regarding the implementation of the Cooperative Learning method (X) and documentation to obtain data regarding student activity (Y) in PAI learning in grades 3 and 4 at MI Fathan Mubina for the 2022-2023 academic year. the number of research subjects was 16 respondents. The results of this research data are said to provide an increase with evidence that the initial percentage of active students in class 4 was 30,8% to 87.5% and in class 3 the initial percentage was seen at 47.5% to 96,3%. The results of implementing the Cooperative Learning method in PAI subjects for students in grades 3 and 4 at MI Fathan Mubina for the 2022-2023 academic year have increased by 50%. With the increase in students' enthusiasm in asking questions, giving opinions and responding to classroom learning, the application of this method helps students who do not understand the lesson more easily because of the motivation of their group friends. It is hoped that this research can provide information and input for learning activities in schools, especially at MI Fathan Mubina.